Surgical considerations towards inducing proprioceptive feedback in dental implants - Das, Siddhartha; Ghosh, Subhashis; Tu, Qisheng; Zhu, Zoe Xiaofang; Chen, Jake Jinkun (Scientific reports, 2025)
Periodontal ligament (PDL) consists mainly of collagen fiber bundles with specialized mechanoreceptors and free nerve endings that connect the cementum of the tooth root to alveolar bone and are vital for dental proprioceptive function. When a tooth is lost and replaced with a dental implant, osseointegration occurs without the intervening PDL, leading to a loss of proprioceptive function. Herein we report the placement, and healthy integration of an advanced dental implant in the socket of rat study models without facilitating the process of osseointegration, that could possibly impart proprioceptive features comparable to those noted in natural teeth. The experimental surgical procedure during dental implant installation in rat models involved various oral tissue structures surrounding the teeth as analogous to those in human subjects and therefore bears a significant clinical relevance. Additionally, the surgical procedure detailed here confers the advantages of its use to investigate not only dental implants but also could be explorative for a wide range of extra-oral implants for improved neural integration.